Lane, Franklin County - Engle, Erinn (Kansas State University, The Chapman Center for Rural Studies, 2016)
As the stage for Bleeding Kansas, Lane, Kansas in Franklin County’s Pottawatomie Township has seen times of violent bloodshed, times of booming prosperity, and times of quiet solitude. Lane has a rich history of business, community, and above all, steady persistence. This study uses maps, historic images, and on-site photography as references for reading.
Erinn Engle, “Lane, Franklin County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/177.
Keywords: Avondale; Gen. James Lane; Franklin County; Ottawa; Peoria; James A. Miles